Schooling Quality in Eastern Europe: Educational Production During Transition - Andreas Ammermüller; Hans Heijke; Ludger Wößmann (Kiel Institute for World Economics (IfW), 2003)
We estimate educational production functions for seven Eastern European transition countries, using student-level TIMSS data for lower secondary education. The results show substantial effects of student background on educational performance and a much lower impact of resources and the institutional setting. Two different groups of countries emerge. For the first group that features high mean test scores and has progressed far in transition, large effects of family background on student performance and a higher spread of test scores illustrate the similarity to Western European schooling systems, the performance of which it surpasses. Schools of the second group produce instead a denser distribution of educational achievement, characteristic of communist societies.
Keywords: P36; I21; 330; Educational production; class size; TIMSS; transition of institutions; Bildungsniveau; Allgemeinbildende Schule; Familiensoziologie; Übergangswirtschaft; Schätzung; Osteuropa; Klassengröße; TIMSS